Descending Necrotizing Mediastinitis Caused by Streptococcus pyogenes in a Child with Primary Epstein–Barr Virus Infection - Miki Yoshimura; Tomoo Daifu; Minoru Suehiro; Tsuyoshi Shoji; Yoshihisa Higuchi (Pediatric Reports, 2022)
Descending necrotizing mediastinitis (DNM) is a severe, life-threatening disease with a high mortality rate resulting from sepsis or other complications. DNM can also be a rare and severe complication of Epstein–Barr virus (EBV) infection in adolescents and young adults but has never been reported in a pre-school child. A 4-year-old girl was admitted to our hospital with a 2-day history of fever and chest pain. Computed tomography (CT) revealed a right sided pleural effusion, fluid collection in the retropharyngeal and mediastinal areas, cervical lymphadenopathy, and marked hepatosplenomegaly. She was diagnosed with empyema, retropharyngeal abscess, and mediastinitis. To improve her dyspnea, a chest tube was inserted, and antibiotic treatment was initiated. Her condition improved temporarily, but on day 5 in our hospital, she developed a fever again. A repeat CT scan showed exacerbation of fluid retention in the retropharyngeal area and the mediastinum, for which she underwent drainage and debridement of necrotic tissue in the retropharynx and mediastinum. The presence of cervical lymphadenopathy and marked hepatosplenomegaly suggested the involvement of EBV. Serological tests for EBV revealed primary EBV infection at the time of the DNM onset. Finally, she was diagnosed with DNM following primary EBV infection. At follow-up 1 year later, she was doing well. The risk of DNM should be recognized in patients, even pre-school aged children, with primary EBV infection.